Effect of cap-assisted esophagogastroduodenoscopy on examination of the major duodenal papilla: a noninferior, randomized controlled trial - Shi, Xin; Luo, Hui; Ning, Bo; Wang, Xiangping; Tao, Qin; Liang, Shuhui; Zhang, Rongchun; Chen, Jie; Luo, Bing; Yao, Shaowei; Pan, Yanglin; Guo, Xuegang; Fan, Daiming (Endoscopy, 2019)
Background Cap-assisted esophagogastroduodenoscopy (CA-EGD) using a transparent cap fitted to the tip of the scope has emerged as an alternative method for examination of the major duodenal papilla (MDP). However, it remains unclear whether CA-EGD is noninferior to standard duodenoscopy for MDP examination. The aim of this study was to compare the efficacies of the two methods for complete examination of the MDP.Methods This prospective, noninferior, randomized controlled study was conducted at two endoscopy centers. Consecutive patients who underwent endoscopic retrograde cholangiopancreatography were randomized (1:1) to undergo CA-EGD or standard duodenoscopy for MDP examination. The primary outcome was complete examination of the MDP, defined as visualization of the upper end, opening, and lower end of the papilla. Secondary outcomes included endoscopic findings and the time taken for the MDP examination.Results The study was terminated for futility after the interim analysis. A total of 171 patients were randomly allocated to CA-EGD (n = 85) or standard duodenoscopy (n = 86). The baseline characteristics were comparable between the two groups. Complete examination of the MDP was achieved in 58/85 patients (68.2 %) in the CA-EGD group and in 74/86 (86.0 %) in standard duodenoscopy group. The difference in proportions was – 17.81 percentage points (95 % confidence interval [CI] –28.14 to –7.48) by intention-to-treat analysis and – 18.22 percentage points (95 %CI –28.34 to –8.10) by per-protocol analysis, both of which were significantly lower than the noninferiority margin of –5 %, and therefore the noninferiority of CA-EGD could not be confirmed. Examination time was significantly longer with CA-EGD (69.5 [SD 46.4] vs. 33.0 [SD 28.9] seconds; P < 0.001).Conclusions Although complete examination of the MDP can be achieved by CA-EGD in most patients, it could not replace duodenoscopy as the standard method for examination of the MDP.